Artificial intelligence research in organizations: a bibliometric approach - Peng Liu; Yangjie Lai; Dege Liu (Cogent Business & Management, 2024)
Although more and more researchers have paid attention to artificial intelligence research in organizations across different subdivided fields in recent years, there is still a lack of integrative and comprehensive research on AI in organizations. Building upon previous quantitative and qualitative studies in the artificial intelligence literature, this study presents a bibliometric analysis of articles on artificial intelligence in the fields of management, business, and applied psychology up to June 2nd, 2023. The research explores the landscape of artificial intelligence articles, highlighting key intellectual contributions and research constituents such as journals, authors, countries, institutions, and topics. Additionally, the study investigates the intellectual structure and overlay visualization of keywords to identify popular topics and trends in recent artificial intelligence research. The findings offer readers a systematic understanding of artificial intelligence development and provide new insights that expand upon existing knowledge in artificial intelligence within management, business, and applied psychology.
Keywords: 650; Artificial intelligence; bibliometric review; VOSviewer; scientific visualization; landscape